PENGARUH MENGUNYAH BUAH NANAS DAN BELIMBING TERHADAP SKOR PLAK PADA PASIEN PERAWATAN ORTHODONSI CEKAT DI KLINIK GIGI ALAMANDA YOGYAKARTA - Diah Wijayanti Sutha; Susilarti Susilarti; Ta’adi Ta’adi (Poltekkes Kemenkes Yogyakarta, 2015)
Plaque is the main cause of damage teeth. For the user oforthodonthic, mild inflammatory caused by plaque will bemore severe because leftover food attached to braceseasier and difficult to clean. Chew pineapple and starfruitmake mechanical motion of the teeth because of thechewingnecessity longer to the fibrous food, more overthe adictic of pineapple and starfruit can help ini increasingsaliva. So that can reduce plaque and remove the leftoverfood between the teeth, so can avoid fromdemineralization.To determine the effect of chewing pineapplesand starfruits to care oforthodontic patient.Research done by using Quasi eksperiment study. Locationand implementation research taken at Alamanda DentalClinic Yogyakarta in June until September 2012 with thecare of orthodontic population of patient at Alamanda DentalClinic Yogyakarta. The samples used was 40, takenwith Quota Sampling technic. The variable of influenceswere chewing fruits, the variable of influences was plaquescore. Analysis of the data used was Paired Sample t-testwith significancy level = 0,05. Result of the study showedthe number of respondent distribution before chewing pineapplethere was 18 respondent with the percentage 90%had criteria of score medium plaque, 2 respondent withthe percentage 10% had criteria of score bad plaque. Afterconsumed pineapple, plaque score with good criteriaaccupied the highest position, viz.16 respondents with thepercentage 80% and the next was plaque score with mediumcriteria, viz. 4 respondents with the percentage 20%,In intervensi chewing the starfruits group, there was 18respondent with the percentage 10% had the criteria ofscore bad plaque. After consumed starfruits, plaque scorewith good criteria accupied the highest position, viz. 17respondents with the percentage 85% and the next wasplaque score with medium criteria, viz. 3 respondents withthe percentage 15%. From the statistical paired sample ttest,the result was p=0,000 (p value=0,05) it means therewas an effect for consumed pineapples and starfuits inplaque score to care of orthodontic patient. Conclusion isthere was effect for consumed pineapples and starfruitsin plaque score to care of orthodontic patient at AlamandaDental Clinic Yogyakarta with significant score from theresult of Paired sample t-test p=0,000 (p value<0,005).